The Metalloprotease Meprin β Is an Alternative β-Secretase of APP - Becker-Pauly, Christoph; Pietrzik, Claus U. (Frontiers in Molecular Neuroscience, 2017)
The membrane bound metalloprotease meprin β is important for collagen fibril assembly in connective tissue formation and for the detachment of the intestinal mucus layer for proper barrier function. Recent proteomic studies revealed dozens of putative new substrates of meprin β, including the amyloid precursor protein (APP). It was shown that APP is cleaved by meprin β in distinct ways, either at the β-secretase site resulting in increased levels of Aβ peptides, or at the N-terminus releasing 11 kDa and 20 kDa peptide fragments. The latter event was discussed to be rather neuroprotective, whereas the ectodomain shedding of APP by meprin β reminiscent to BACE-1 is in line with the amyloid hypothesis of Alzheimer’s disease, promoting neurodegeneration. The N-terminal 11 kDa and 20 kDa peptide fragments represent physiological cleavage products, since they are found in human brains under different diseased or non-diseased states, whereas these fragments are completely missing in brains of meprin β knock-out animals. Meprin β is not only a sheddase of adhesion molecules, such as APP, but was additionally demonstrated to cleave within the prodomain of ADAM10. Activated ADAM10, the α-secretase of APP, is then able to shed meprin β from the cell surface thereby abolishing the β-secretase activity. All together meprin β seems to be a novel player in APP processing events, even influencing other enzymes involved in APP cleavage.